Pengaruh Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU), dan Dana Alokasi Khusus (DAK) terhadap Belanja Modal dengan Pendapatan Per Kapita sebagai Variabel Pemoderasi - Suryatiningrum, Ika; Indarti, Iin; Adnanti, Wenny Ana (STIE Widya Manggala, 2020)
Regional autonomy and fiscal decentralization give local governments the authority to explore revenue and perform the role of allocation independently in settingdevelopment priorities in which there is a component of capital expenditure. This research aimed to examine and analyze the effect of Own Source Revenue, General Allocation Fund, and Special Allocation Fund on Capital Expenditure that are moderated by Percapita Income in Regency/City Governments in Central Java Province. The population of this research were the Regency / City Governments in Central Java which consists of 29 Regencies and 6 Cities in 2013 - 2017. The sampling technique used was saturated sampling. The secondary data was collected from APBD Realization Reports and Per Capita GRDP Tables in 2013-2017. The data analysis technique used were Multiple Regression Analysis and Moderated Regression Analysis (MRA). The results showed that Own Source Revenue, General Allocation Fund and Special Allocation Fund, both partially and simultaneously had a significant positive effect on Capital Expenditure. Per Capita Income as a moderating variable can strengthen the effect of Own Source Revenue on Capital Expenditure, but it cannot strengthen the effect of General Allocation Fund and Special Allocation Fund on Capital Expenditure.